2014
DOI: 10.15302/j-fase-2014039
|View full text |Cite
|
Sign up to set email alerts
|

Detection of genomic signatures for pig hairlessness using high-density SNP data

Abstract: Hair provides thermal regulation for mammals and protects the skin from wounds, bites and ultraviolet (UV) radiation, and is important in adaptation to volatile environments. Pigs in nature are divided into hairy and hairless, which provide a good model for deciphering the molecular mechanisms of hairlessness. We conducted a genomic scan for genetically differentiated regions between hairy and hairless pigs using 60K SNP data, with the aim to better understand the genetic basis for the hairless phenotype in pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…The formula for F ST was:FST=MSPMSGMSP+(nC1)MSG where MSP and MSG denote the observed mean square errors for loci between and within populations, respectively, and nC is the average sample size across samples that also incorporates and corrects for the variance in sample size over the population. More details are shown in Su et al [27]. The top 1% of SNPs were defined as significant [28].…”
Section: Methodsmentioning
confidence: 99%
“…The formula for F ST was:FST=MSPMSGMSP+(nC1)MSG where MSP and MSG denote the observed mean square errors for loci between and within populations, respectively, and nC is the average sample size across samples that also incorporates and corrects for the variance in sample size over the population. More details are shown in Su et al [27]. The top 1% of SNPs were defined as significant [28].…”
Section: Methodsmentioning
confidence: 99%
“…Lemus-Flores et al (2020), on the other hand, report the EHF, DST, PDE8A, FOXA1, and VCL genes in YBHP compared to the Duroc breed. Su et al (2014) note that RB1 and BAMBI genes are associated with the lack of hair in USYU and Mexico hairless pigs. Jiang et al (2019) report the MAP2 (HR) and FOXI3 genes as candidate markers, considering that hair follicle morphogenesis occurs at an early stage of embryo development, like in humans and mice.…”
Section: Discussionmentioning
confidence: 91%
“…Those genes were found to cluster in two primary categories including biological process and molecular function ( Figure 4 A). The pathway enrichment analysis within the 5% genomic regions revealed that these genes were forcefully in connection with extreme environment adaptation-related pathways, including tight junction [ 27 , 28 ], notch signaling [ 29 , 30 , 31 ], vascular smooth muscle contraction [ 32 ], and RIG-I-like receptor signaling [ 33 , 34 ] ( Figure 4 B and Table 1 ). Within the consistent A/B compartment-switching regions, a series of genes related to cell proliferation and differentiation were identified in the tight junction, notch signaling, and RIG-I-like receptor signaling pathways.…”
Section: Resultsmentioning
confidence: 99%